2021
DOI: 10.2147/ijwh.s301804
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Care of Victims of Interpersonal Violence and Rape in Tanzania: A Qualitative Investigation

Abstract: Introduction: Africa has high rates of interpersonal violence and rape, although little is known about how these cases are handled in the clinical setting. Methods: We enrolled 121 health care professionals and students in Tanzania from the fields of midwifery, nursing and medicine, and conducted 18 focus group discussions stratified by both professional and clinical experience. Two clinical scenarios were presented across all groups and participants were asked to give their opinions on how the hospital they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“… 12 HCP training needs for working with SGBV survivors have also been identified in Kenya 14 and Tanzania. 11 In Kenyan humanitarian 13 and non-humanitarian 10 contexts, SGBV survivors reported concerns regarding HCP confidentiality and fears of community stigma. 13 A recent study with women sexual violence survivors from Somalia and Syria noted the need for additional research to understand sexual violence stigma in health care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 HCP training needs for working with SGBV survivors have also been identified in Kenya 14 and Tanzania. 11 In Kenyan humanitarian 13 and non-humanitarian 10 contexts, SGBV survivors reported concerns regarding HCP confidentiality and fears of community stigma. 13 A recent study with women sexual violence survivors from Somalia and Syria noted the need for additional research to understand sexual violence stigma in health care.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Further information on effective strategies to train HCPs in humanitarian contexts is required to ensure youth-friendly post-rape care experiences. 9 The need for youth-friendly post-rape care training with HCPs has been identified in East African contexts, 10,11 including within conflictaffected regions. 3,12,13 A study with HCPs from conflict-affected Gulu District in Uganda found that inadequate training opportunities and policies within health facilities contributed to a lack of confidence when working with SGBV survivors.…”
mentioning
confidence: 99%
“…Healthcare providers (HCPs) play a critical role in accessing and delivering SRH services. While HCPs face facility-level challenges to highquality care, such as a lack of private rooms to ensure privacy and confidentially, high volumes of patients, scheduling issues, and a lack of specific SRH services and equipment (Mgopa et al, 2021c), studies demonstrate that individuallevel factors such as the religious and cultural background of HCPs may also impact care delivery (Mgopa et al, 2021b). Many patients have reported SRH services being inaccessible due to a lack of confidentiality, privacy, discrimination, stigma, and negative attitudes toward HCPs (Ross et al, 2021).…”
Section: Introductionmentioning
confidence: 99%